2014
DOI: 10.1557/jmr.2014.163
|View full text |Cite
|
Sign up to set email alerts
|

Laser-deposited CoCrMo alloy: Microstructure, wear, and electrochemical properties

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Preliminary investigation on the corrosion characteristics of SLM CoCrW and DLD CoCrMo alloys were reported by Lu, et al, 137 and Mantrala, et al, 138 respectively. Both studies intended to correlate the laser parameters utilized in each manufacturing process with corrosion performance.…”
Section: Titanium Alloysmentioning
confidence: 97%
See 2 more Smart Citations
“…Preliminary investigation on the corrosion characteristics of SLM CoCrW and DLD CoCrMo alloys were reported by Lu, et al, 137 and Mantrala, et al, 138 respectively. Both studies intended to correlate the laser parameters utilized in each manufacturing process with corrosion performance.…”
Section: Titanium Alloysmentioning
confidence: 97%
“…The findings from such studies are summarized in Table 7. [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148] In the case of CoCr, Xin, et al, 133 investigated the corrosion characteristics of SLM CoCr in artificial saliva solution-due to the applicability of CoCr-based alloys in odontology-and compared the results with a cast counterpart. The SLM CoCr (i corr = 0.02 μA/cm 2 ) exhibited similar corrosion characteristics to cast (i corr = 0.07 μA/cm 2 ) from potentiodynamic polarization in the analyzed environment.…”
Section: Titanium Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased hardness of CoCrMo due to the laser-induced fine and homogenous microstructure has been reported by a number of authors [18,19,23,24]. Since no nitride was detected in XRD, the possibility of hardness increment due to the nitride formation can be ruled out.…”
Section: Surface Phase Structure Analysismentioning
confidence: 89%
“…The CoCrMo parts created by the SLM process exhibited superior hardness than those produced by conventional manufacturing processes (e.g., casting, electron beam melting and forging). Mantrala et al created a CoCrMo layer using the laser-engineered net shaping (LENS) technique [24]. They reported that the microstructural features, as well as the hardness and wear properties strongly depended on the laser processing parameters.…”
Section: Introductionmentioning
confidence: 99%